Pengaruh Edukasi Kesehatan Breastfeeding Father Terhadap Keberhasilan ASI Eksklusif di Klinik Yapida Gunung Putri - Nur Zarit Ayya Sofi; Ita Herawati (Universitas Aisyah Pringsewu (UAP) Lampung, 2022)
The success of breastfeeding is largely determined by the father's role as a breastfeeding father, because the father will also determine the milk-excretion reflex (let down reflex) which is strongly influenced by the mother's emotional state or feelings. Research Objectives are to determine the effect of breastfeeding father's health education on the success of exclusive breastfeeding at the Yapida Gunung Putri Clinic in 2022 period. This study uses an observational analytical research method with a case control design. The sampling technique was carried out by accidental sampling with a sample of 20 subjects in each group. Bivariate analysis using chi square test by looking at the Odds Ratio (OR). The results of bivariate analysis showed that mothers who were given a breastfeeding father were associated with the success of exclusive breastfeeding (p = 0.010; OR = 7.429), meaning that mothers who were given a Breastfeeding Father were more in the case group. Mothers who are not given a Breastfeeding Father are less likely to succeed in exclusive breastfeeding. It can be concluded that there is a significant relationship between the influence of breastfeeding father's health education and the success of exclusive breastfeeding in the Kinik Yapida Gunung Putri area. It is recommended to husbands to be more supportive of mothers towards the success of exclusive breastfeeding. Abstrack : Keberhasilan menyusui sangat ditentukan oleh peran ayah sebagai breastfeeding father, karena ayah akan turut menentukan refleks pengeluaran ASI (let down refleks) yang sangat dipengaruhi oleh keadaan emosi atau perasaan ibu. Tujuan Penelitian ini untuk Mengetahui pengaruh edukasi kesehatan breastfeeding father terhadap keberhasilan ASI Eksklusif di Klinik Yapida Gunung Putri periode 2022. Penelitian ini menggunakan metode penelitian analitik observasional dengan desain case control. Teknik pengambilan sampel dilakukan dengan cara Accidental sampling dengan jumlah sampel 20 subyek pada setiap kelompok.Analisis bivariat menggunakan uji chi square dengan melihat Odds Ratio (OR). Hasil analisis bivariat menunjukkan bahwa ibu yang diberikan breastfeeding father berhubungan dengan keberhasilan ASI Eksklusif (p=0.010;OR=7.429), artinya ibu yang diberikan Breastfeeding Father lebih banyak pada pada kelompok kasus. Ibu yang tidak diberikan Breastfeeding Father cenderung tidak berhasil ASI Eksklusif. Dapat disimpulkan bahwa terdapat hubungan yang bermakna antara pengaruh dilakukannya edukasi kesehatan breastfeeding father dengan keberhasilan ASI Eksklusif di wilayah Kinik Yapida Gunung Putri. Disarankan kepada Suami lebih mendukung Ibu terhadap keberhasilan ASI Eksklusif.